Diseases Resistance and Enzymatic Changes in Pseudomonus aeruginosa Infected Clarias gariepinus treated with Carica Papaya root extracts - Ukwe, I.O.K., Vopnu, F. B. (Journal of Medical Care Research and Review, 2021)
One hundred and twenty Clarias gariepinus were infected intramuscularly with 1.0ml of P. aeruginusa (4.1x104cfu) using 2ml injection syringe and observed in the laboratory for diseases presence. After diseases presence, they were distributed into four groups in triplicate and treated with various level of carica papaya aqueous root extracts (0.0ml, 1.0ml, 2.0ml, and 3.0m), to determine in the disease resistant ability and therapeutic effect on the enzymatic activities of the infected fish using the experimental extract. Blood samples were collected before the infection, after diseases presence and day 2, 5 and 7 of the treatment with experimental extract for biochemical analysis to determine changes in following the enzymes; aspartate transaminiase (AST), alanin transaminas (ALT), alkaline phosphare (ATP) and Acid phosphare (ACP) across the various treatments (0.0ml, 1.0ml, 2.0ml and 3.0ml). And the disease resistance ability of the experimental extract was determined at the end of day 7 of the experiment. At the end of the experiment, it was observed that the activities of; AST, ALT, ATP and ACP were higher (P>0.05) after the infection compared to the activities before the infection. After day 2 of the treatment, the activities of all the analysed enzymes were lower (P<0.05) in the treated groups (1.0 – 3.0ml) compared to the values in the untreated group (0.0ml), the same trend was observed at end of day 5. At the end of day 7, the values of the AST and ALT were higher in the infected fish treated with 2.0ml and 3.0ml of the extract compared to the untreated group (0.0ml), but the ALP and ACP values were lower in the treated group compared to be untreated. The disease resistance ability which is a measure of the relative survival percentage was 0% (zero percent) in the untreated group compared to 100% in the treated groups. Keywords: Disease resistance, enzymatic change, P. aeruginosu, C. gariepinus, carica papaya root extract